An infinity of things : how Sir Henry Wellcome collected the world - Larson, Frances, 1976- (Oxford University Press, 2009)
An Infinity of Things tells the story of one of the largest private collections ever created, and the life of the man behind it. Wellcome planned a great museum filled with treasures from all corners of the globe, charting the history of human health from prehistory to the present day. The breadth of his vision was matched only by the depth of his pockets. During the opening decades of the twentieth century he acquired a collection so large that later generations of staff took to describing its contents by the ton. But Wellcome's museum was never finished, and his collection was still stored i.